3D Timeline: Reverse engineering of a part‐based provenance from consecutive 3D models. (1st June 2014) - Doboš, Jozef; Mitra, Niloy J.; Steed, Anthony
Abstract: We present a novel tool for reverse engineering of modeling histories from consecutive 3D files based on a timeline abstraction. Although a timeline interface is commonly used in 3D modeling packages for animations, it has not been used on geometry manipulation before. Unlike previous visualization methods that require instrumentation of editing software, our approach does not rely on pre‐recorded editing instructions. Instead, each stand‐alone 3D file is treated as a keyframe of a construction flow from which the editing provenance is reverse engineered. We evaluate this tool on six complex 3D sequences created in a variety of modeling tools by different professional artists and conclude that it provides useful means of visualizing and understanding the editing history. A comparative user study suggests the tool is well suited for this purpose.